Design in sport: development of an equestrian tool with a focus on ergonomics (Human Factors in Design, 2021)
The importance of ergonomics in product design is well known today, however, it is even more evident in the area of sport, where anthropometric adjustments can prevent injuries and/or contribute to improve the performance of athletes. Supported by the relevance of design in sports, this article aims to present the development of an aid tool in the handling of the reins in the horse, providing more safety and control to the rider during the practice of equestrian and contributing to a better performance of the horse during training. The product was developed in constant iteraction with users, through successive rounds of Task Analysis, and, by incorporating ergonomic aspects, it intends to contribute to making the practice of horse riding more comfortable for its practitioners.
Keywords: Design; Sports; Equestrianism; Ergonomics